Structural design and analysis of a one-way drive clutch for printers. (October 2020) - Liu, Pingping; Wen, Guang; Zuo, Fangjun; Deng, Xingyue
Abstract: Based on the application background of the paper reversing function of a duplex printer, a clutch which can realize one-way transmission is designed. The driving gear and driven gear are dynamically connected by a connector with wedge teeth and spiral slope. When the motor rotates forward, the clutch can normally output power to the load, and when the motor reverses, the power is cut off, and the load cannot rotate. The clutch can not only realize the paper reversing function, but also make the load not rotate with the reverse of the motor, so as to protect the toner cartridge and heating roller. The clutch has the advantages of few parts, low cost, convenient installation, compact structure and low noise after assembly. In addition, on the basis of the structural design, the necessary mechanical properties of the clutch are analyzed to provide theoretical support for structural improvement.